Rewarming rate of hypothermic neonates in a low-resource setting: a retrospective single-center study - Rossi, Elisa; Maziku, Donald Micah; Leluko, Dionis Erasto; Guadagno, Chiara; Brasili, Luca; Azzimonti, Gaetano; Putoto, Giovanni; Pietravalle, Andrea; Cavallin, Francesco; Trevisanuto, Daniele (Frontiers in Pediatrics, 2023)
Background: Hypothermic neonates need to be promptly rewarmed but there is no strong evidence to support a rapid or a slow pace of rewarming. This study aimed to investigate the rewarming rate and its associations with clinical outcomes in hypothermic neonates born in a low-resource setting. Methods: This retrospective study evaluated the rewarming rate of hypothermic inborn neonates admitted to the Special Care Unit of Tosamaganga Hospital (Tanzania) in 2019-2020. The rewarming rate was calculated as the difference between the first normothermic value (36.5-37.5°C) and the admission temperature, divided by the time elapsed. Neurodevelopmental status at 1 month of age was assessed using the Hammersmith Neonatal Neurological Examination. Results: Median rewarming rate was 0.22°C/hour (IQR 0.11-0.41) in 344/382 (90%) hypothermic inborn infants, and was inversely correlated to admission temperature (correlation coefficient -0.36, p<0.001). Rewarming rate was not associated with hypoglycemia (p=0.16), late onset sepsis (p=0.10), jaundice (p=0.85), respiratory distress (p=0.83), seizures (p=0.34), length of hospital stay (p=0.22) or mortality (p=0.17). In 102/307 survivors who returned at follow-up visit at 1 month of age, rewarming rate was not associated with a potential correlate of cerebral palsy risk. Conclusions: Our findings did not show any significant association between rewarming rate and mortality, selected complications or abnormal neurologic exam suggestive of cerebral palsy. However, further prospective studies with strong methodological approach are required to provide conclusive evidence on this topic.